DONALD TRUMP, EROPA, ASIA DAN ISLAM - Herdi Sahrasad (The Indonesian Islamic Studies and International Relations Association (Insiera), 2017)
US presidential election in 2016 had brought Donald Trump to the oval office. Compare to the regime before, Trump would make US approaches to its counterparts more hard and firm. In this context, Trump would possibly raise the conflict tense towards China and Islamic World since the US would tend to utilise hard rather than soft power. Trump never pictured clearly his foreign policy direction, but he indicated to prefer isolationism and protectionism. He did not have foreign policy record so that US foreign policy would be very relying on Trump’s rhetorical campaigns. The eccentric leadership of US President Donald Trump is a unique global phenomena which very interesting to be discussed.